Asthma and obstructive sleep apnoea in adults and children – an up-to-date review. (February 2022) - Wang, Ran; Mihaicuta, Stefan; Tiotiu, Angelica; Corlateanu, Alexandru; Ioan, Iulia Cristina; Bikov, Andras
Summary: Obstructive sleep apnoea (OSA) and asthma are two common respiratory disorders in children and adults. Apart from common risk factors, such as obesity, gastroesophageal reflux disease and allergic rhinitis, emerging evidence suggest that the two diseases may complicate the clinical course of each other. On one hand, OSA modifies asthmatic airway inflammation and is associated with poor asthma control. On the other hand, asthma and its medications increase the collapsibility of the upper airways contributing to the development and worsening of OSA. The overnight respiratory symptoms of OSA and asthma are often similar, and an inpatient polysomnography is often necessary for a proper diagnosis, especially in children. Continuous positive pressure, the gold standard treatment for OSA can improve asthma control in patients suffering from both diseases. However, there is limited evidence how anti-asthma medications act in the same patients. Nevertheless, adenotonsillectomy seems to be effective in children with concomitant asthma and OSA. This review summarises the evidence for the bidirectional link between asthma and OSA, focuses on diagnostic and therapeutic challenges and highlights the need for further research.